Cholesterol side chain analogs but not its ether analogs possess cholesterol-lowering activity. Issue 2 (23rd December 2014) - Lei, Lin; Wang, Xiaobo; Huang, Weihuan; Liu, Yuwei; Zheng, Fangrui; Ma, Ka Ying; Li, Yuk Man; Wang, Lijun; Man, Sun Wa; Zhang, Chengnan; Chen, Zhen-Yu
Abstract : SI is hypocholesterolemic with little absorption, while CE and CM are well absorbed and have no effect on plasma cholesterol. Abstract : Cholesterol analogs can be used to treat hypercholesterolemia. The present study was to test the effects of cholesteryl 3β-ethoxy (CE) and cholesteryl 3β-methoxy (CM) on plasma total cholesterol (TC) compared with that of β-sitosterol (SI) in hamsters fed a high cholesterol diet. CM and CE are the methoxy and ethoxy analogs of cholesterol while SI is an analog of cholesterol having an additional ethyl group on the side chain. Results showed that SI at a dose of 0.1% could effectively reduce plasma TC by 18%. The analysis of sterols in the plasma and liver did not detect the presence of SI, proving that it was poorly absorbed in the intestine. In contrast, both CE and CM had no effect on plasma TC. However, CE and CM were found to accumulate in both plasma and liver, indicating that they could be well absorbed in the intestine. It was therefore concluded that analogs having different side chains possessed plasma TC-lowering activity, while analogs or derivatives on the hydroxyl group had no hypocholesterolemic activity.